1995
DOI: 10.1109/20.489586
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced remanence in flash-annealed Nd/sub 4/Fe/sub 78/B/sub 18/

Abstract: A b s t r a c t -N a n o c r y s t a l l i n e N d q F e 7 g B 1 8 w a s produced by affixing current leads directly to amorphous ribbons for flash-annealing. Ribbons were annealed in the range Ta = 650-10OO0C, for times 10-600 s. Flash-annealed ribbons show higher remanence ratios (Mr/Ms 0.83) than those submitted to conventional furnace (68O0C/1O min) annealing ( M r / M e 0.74). In flash-annealed ribbons, Mossbauer spectroscopy and xr a y d i f f~a c~~o n indicated the presence of the Nd2Fe23B3 phase, in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…• C. [1][2][3][4][5][6][7][8][9][10] The alloys showing such hard magnetic properties are composed of large amounts of soft magnetic particles such as Fe 3 B, RE 2 Fe 23 B 3 and α-Fe and small amounts of hard magnetic RE 2 Fe 14 B particles exhibiting large magnetocrystalline anisotropy. 9,11,12) The magnetic properties of these alloys depend on the phases precipitated, the grain size, the distribution and the interphase boundary structures between hard and soft magnetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…• C. [1][2][3][4][5][6][7][8][9][10] The alloys showing such hard magnetic properties are composed of large amounts of soft magnetic particles such as Fe 3 B, RE 2 Fe 23 B 3 and α-Fe and small amounts of hard magnetic RE 2 Fe 14 B particles exhibiting large magnetocrystalline anisotropy. 9,11,12) The magnetic properties of these alloys depend on the phases precipitated, the grain size, the distribution and the interphase boundary structures between hard and soft magnetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the deviation was small and oscillatory, as we have observed here, for the low Nd alloy where there is believed to be substantial exchange coupling. An oscillatory Henkel plot was observed for thermally demagnetized nanocrystalline Nd 4 Fe 78 B 18 by Altoé et al 10 This behavior was contrasted to that of MQII which showed strong magnetizing interactions. Thus, an oscillatory Henkel plot has been observed for high remanence materials belonging to the three major systems.…”
Section: Resultsmentioning
confidence: 95%
“…Henkel plots for an ac demagnetization show both magnetizing and demagnetizing regions, as was observed previously in Nd 9 Fe 85 B 6 ͑␣-FeϩNd 2 Fe 14 B͒ 2 and Nd 4 Fe 78 B 18 . 10 The data were compared to the moving Preisach model. Preliminary calculations indicate the necessity to consider both meanfield and random interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kramer and co-workers [5] found that in Rietveld analysis of the X-ray data [6]. 57 Fe Mössbauer spectra were recorded at room temperature, with absorbers made up of ribbons glued side by side on a lucite disk.…”
Section: Introductionmentioning
confidence: 99%